Five- and seven-year outcomes for image-guided moderately accelerated hypofractionated proton therapy for prostate cancer. (3rd April 2022) - Henderson, Randal H.; Bryant, Curtis M.; Nichols, R. Charles; Mendenhall, William M.; Hoppe, Bradford S.; Su, Zhong; Morris, Christopher G.; Mendenhall, Nancy P.
Abstract: Background: To report 5- and 7-year outcomes after image-guided moderately accelerated hypofractionated proton therapy (AHPT) for prostate cancer. Material and methods: We reviewed the first 582 prostate cancer patients enrolled on prospective outcomes tracking trial and treated with double-scattered moderately AHPT between 2008 and 2015. 269 patients had low-risk (LR) and 313 had intermediate-risk (IR) disease, including 149 with favorable intermediate-risk (FIR) and 164 with unfavorable intermediate-risk (UIR) disease. LR patients received a median 70.0GyRBE (2.5GyRBE/fraction) and IR patients received a median of 72.5 GyRBE. Seventeen patients (UIR, n  = 12) received androgen deprivation therapy (ADT) for a median of 6 months. Toxicities were graded per the CTCAE, v4.0, and patient-reported quality-of-life data were reviewed. Results: Median follow-up was 8.0 years (0.9–12.2). The 5- and 7-year rates of freedom from biochemical progression (FFBP) overall and in the LR and IR subsets, respectively, were 96.8/95.2%, 98.8/98.8%, and 95.0/91.9%. For the FIR and UIR subsets, they were 97.2/95.2% and 93.1/88.8%. Actuarial 5- and 7-year rates of late CTCAE, v4.0, grade 2 gastrointestinal (GI), grade 3 GI, and grade 3 genitourinary (GU) toxicities were 9.9%/11.2%, 1.4/1.4% and 1.3/2.1%, respectively. No grade ≥4 GI or GU toxicities occurred. The mean (standard deviation, SD) IPSS and EPIC Composite bowel function and bother scores were 7 (SD = 5), 97 (SD = 7), and 94 (SD = 6), respectively at baseline, 7 (SD = 5), 92 (SD = 13), and 92 (SD = 9) at the 5-year follow-up, and 7 (SD = 5), 93 (SD = 12), and 92 (SD = 10) at the 7-year follow-up. Conclusion: Image-guided AHPT 5- and 7-year outcomes show high efficacy, minimal physician-assessed toxicity, and excellent patient-reported outcomes in this cohort.